KETERAMPILAN MENULIS SISWA DALAM ANTOLOGI CERPEN UNTUK MENINGKATKAN PEMAHAMAN TERHADAP ASPEK PENULISAN CERPEN (Universitas Bengkulu, 2024)
This study was motivated to determine the ability to write short stories through the “Short Story Anthology” class XI students of SMK Negeri 7 Bengkulu City. The objectives to be achieved in this study are to 1) Develop students' writing skills, 2) Open opportunities for students to introduce literary works in writing and 3) Become literacy material in short story anthologies. The type of research used in this study is the Experimental Method. The author conducts direct observation in the classroom and experiments. The subjects of classroom action research are students of class XI SMK Negeri 7 Bengkulu City in the first semester of 2024, totaling 45 students. The results of student writing can be assessed through four aspects, namely 1) Completeness of Formal Aspects, 2) Conformity of EYD, 3) Determination of Writing Works in Fiction and Non-Fiction and 4) From the whole series of research conducted, it can be concluded that there are differences in the results of the assessment of writing short story texts of class XI students of SMK Negeri 7 Bengkulu City. By conducting this research, it is hoped that it can improve writing skills as well as increase literacy understanding in grade XI students of SMK Negeri 7 Bengkulu City about short story texts.